Nathan Sargent correspondence - Sargent, Nathan, 1794-1875.
ALS written by Sargent to Henry A. Wise inviting him to a Whig Party celebration of the Fourth of July in Philadelphia, Pa., and urging him to convince Henry Clay to attend also.
Journalist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clay, Henry, -- 1777-1852.; Wise, Henry A. -- 1806-1876 -- Correspondence; Whig Party (U.S.); Fourth of July; Philadelphia (Pa.) -- Anniversaries, etc; United States -- Politics and government -- 1837-1841.; Journalists